Mastering 3D Printing in the Classroom, Library, and Lab - Horvath, Joan (Apress, 2018)
Learn how to manage and integrate the technology of 3D printers in the classroom, library, and lab. With this book, the authors give practical, lessons-learned advice about the nuts and bolts of what happens when you mix 3D printers, teachers, students, and the general public in environments ranging from K-12 and university classrooms to libraries, museums, and after-school community programs. Take your existing programs to the next level with Mastering 3D Printing in the Classroom, Library, and Lab. Organized in a way that is readable and easy to understand, this book is your guide to the many technology options available now in both software and hardware, as well as a compendium of practical use cases and a discussion of how to create experiences that will align with curriculum standards. You'll examine the whole range of working with a 3D printer, from purchase decision to curriculum design. Finally this book points you forward to the digital-fabrication future current students will face, discussing how key skills can be taught as cost-effectively as possible.